P429 PROGNOSTIC IMPACT OF ROUTINE SIX–MONTH EXERCISE STRESS TEST AFTER COMPLEX LEFT MAIN BIFURCATION PCI. (18th May 2022) - Rigatelli, G; Zuin, M; Gianese, F; Bilato, C; Roncon, L
Abstract: Background/Aim: The prognostic value of the exercise stress after complex stenting of left main (LM) coronary artery bifurcations (LM) disease has been poorly investigated in the modern era. Methods: We retrospectively analysed the procedural and medical data of patients referred to our center for complex LM bifurcation diseas, treated using either single versus dual stenting [Cross–over provisional stenting, T or T–and–Protrusion (TAP), Culotte, and Nano–inverted–T (NIT)] techniques between January 2008 to May 2018. The prognostic impact of an exercise test performed at 6 months during the follow–up period. Results: Five hundred and two patients (316 males, mean age 70.3±12.8 years, mean Syntax score 31.6±6.3) were evaluated. At a mean follow–up of 37.1±10.8 months (range 22.1–47.3 moths), Target lesion failure (TLF) rate was 10.1%. Stent thrombosis and cardiovascular mortality were observed in 1.2% and 3.6% of cases, respectively. A positive exercise test at 6 months of follow–up was detected in 42 out of 502 patients (8.4%) and correlated with angiographic restenosis in 38 patients (7.6%): 7/171patients in Cross–over group (4.1%), 10/61 patients in T or TAP group (16.4%), 15/98 patients in Culotte group (15.3%) and 6/172 patients in NIT group (3.5%). Multivariate Cox regression analysis demonstrated that Age > 75 years (HR 1.45, 95% CI: 1.33–1.58, p = 0.03), dyslipidaemia (HR: 1.68, 95% CI: 1.58–1.72, p < 0.001), eGFR<30 ml/min/1.73 m2 (HR: 1.44, 95% CI: 1.38–1.52, p = 0.04), presence of a triple vessel disease (HR: 1.89, 95% CI: 1.89, 95% CI: 1.84–1.93, p < 0.001), additional ostial LM lesion (HR: 1.75, 95% CI: 1.76–1.81, p < 0.001), additional LM body lesion (HR: 1.33, 95% CI: 1.28–1.36, o < 0.001), a Syntax score > 25 (HR:1.67, 95% CI: 1.61–1.76, p = 0.01), need of Rotablator (HR: 1.66, 95% CI: 1.61–1.75, p = 0.02) and the number of stents implanted (HR: 1.12, 95% CI: 1.08–1.16, p < 0.001) were independent predictors of a positive stress test. Patients reporting a negative exercise test at 6 months of follow–us had a higher freedom from TLF and improved survival compared to those with positive exercise stress test (Figure 1 Panels A and B). Conclusions: A negative exercise performed after 6 months from complex left main stenting predicted excellent outcomes at 3 years follow–up.